Projection of Islamic Doctrinal Values in Anime Naruto 1-3 as Character Formation - Himatul Istiqomah; Muhammad Ihsan Sholeh (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Naruto anime is so popular and favored by many audiences, both the children, teenagers, and adult, men or women. It is not only influenced by uniqueness figures ang a groove the story, but also by magnificence values of Islamic teaching projected very well there. Through this descriptive qualitative research, the researcher aims to analyze whatever values of Islamic teaching projected in Naruto anime 1-3 and its influence on develop the character, by roll of note, observation, an documentation. The result of this research is; It needs enough attention to support children; It needs hard work and courage in order to achieve dreams; And it needs differences to create balance. It has huge influence on establishment of positive character toward audiences. They are not only have entertainments, but also think about the God ways are implied in Naruto anime. So, they will do to be personal, better than ever.